Distribution of the A,B ano h blood group antigens in normal ovarian tissue - Gaskin Urdaneta, Alvia; Davidsohn, Israel (Investigación Clínica, 2013)
The distribution of A, B and H antigens in normal ovaries of 92 patients was studied. The age of the patients varied from premature (1000grams of weight) to adults of 73 years. The study was done using the Red Cell Adherence (RCA) test described by Kovarik, Davidsohn and Stejskal in 1968. We found that only the coelomic epitheJium, the rete ovarii and the mesonephric embyional restcontaín the correspondíng isoantigens. We consider these findings important because Wt: expect that the benign neoplasms arising from these structures contain the blood group substances, while the malignant neoplasms lose them. These findings could possibly be of diagnostic value.